Kinetics Crystallization and Polymorphism of Cocoa Butter throughout the Spontaneous Fermentation Process - Castro Alayo, Efraín Manuelito (2021)
This research was funded by the Consejo Nacional de Ciencia, Tecnología e Innovación Tecnológica-Concytec (Project: Equipamiento Científico 2018-01/E044-2018-01-BM, Contrato N◦ 012-2018-Fondecyt/BM) of the Peruvian Government, The World Bank Group, the Universidad Nacional Toribio Rodríguez de Mendoza de Amazonas and the Pontificia Universidad Católica del Perú. The APC was funded by the Consejo Nacional de Ciencia, Tecnología e Innovación Tecnológica-Concytec